Efecto de un producto comercial a base de compuestos de aceites esenciales (cinamaldehído, carvacrol y timol) y ácidos orgánicos (butirato cálcico y ácido fumárico) microencapsulados sobre los parámetros productivos y calidad de huevo en gallinas de postura en segunda fase de producción - Fernández Lovón, Melany Yordana (2020)
The objective of the study was to evaluate the effects of the inclusion of a commercial product based on microencapsulated essential oil (EA) and organic acid (OA) compounds as an alternative to an antibiotic additive witch improves productive performance (Bacitracin Zinc) in commercial laying hens for a period of 6 weeks on the productive parameters and egg quality. It was used 1008 hens (Hisex Brown) of 54 weeks of age, distributed in three treatments with six repetitions and 56 birds per repetition, to which one of the following experimental diets (treatments) was given: T1, basal diet + 500 mg / kg zinc bacitracin; T2, basal diet + 250 mg / kg (AE + OA); T3, basal diet + 500 mg / kg (AE + OC). The following measurements were made: percentage of total and second egg production, egg weight and mass, feed consumption and feed conversion index, weight gain and mortality as productive parameters; shell and yolk color as well as shell weight as measures of egg quality. The one-way analysis of variance (ANOVA) was performed for the parametric observations and the Kruskal Wallis analysis for the non-parametric data, the difference between means was determined by means of the Tukey test with a confidence level of 95 % (p <0.05). No statistical difference was found for the % of total egg production, % of second-rate egg production, egg mass, feed consumption, feed conversion index and weight gain. However, when evaluating the egg weight, a statistical difference was observed (p <0.014), where T3 (65.07 g) was higher compared to the other treatments T2 (64.64 g) and T1 (63.62). Regarding the data obtained from the evaluation of egg quality, a statistical difference (p <0.003) was found for the yolk color, where treatments T3 (7.97) and T2 (7.94) were better than T1 (7.03). It is concluded that the results obtained from the evaluation of the commercial product based on compounds of essential oils and microencapsulated organic acids are similar to those obtained with APC, with the exception of egg weight and yolk color, where it showed positive results.